Metacognitive reflection and insight therapy (MERIT) for patients with schizophrenia. Issue 2 (25th April 2018) - de Jong, S.; van Donkersgoed, R. J. M.; Timmerman, M. E.; aan het Rot, M.; Wunderink, L.; Arends, J.; van Der Gaag, M.; Aleman, A.; Lysaker, P. H.; Pijnenborg, G. H. M.
Abstract: Background: Impaired metacognition is associated with difficulties in the daily functioning of people with psychosis. Metacognition can be divided into four domains: Self-Reflection, Understanding the Other's Mind, Decentration, and Mastery. This study investigated whether Metacognitive Reflection and Insight Therapy (MERIT) can be used to improve metacognition. Methods: This study is a randomized controlled trial. Patients in the active condition ( n = 35) received forty MERIT sessions, the control group ( n = 35) received treatment as usual. Multilevel intention-to-treat and completers analyses were performed for metacognition and secondary outcomes (psychotic symptomatology, cognitive insight, Theory of Mind, empathy, depression, self-stigma, quality of life, social functioning, and work readiness). Results: Eighteen out of 35 participants finished treatment, half the drop-out stemmed from therapist attrition ( N = 5) or before the first session ( N = 4). Intention-to-treat analysis demonstrated that in both groups metacognition improved between pre- and post-measurements, with no significant differences between the groups. Patients who received MERIT continued to improve, while the control group returned to baseline, leading to significant differences at follow-up. Completers analysis (18/35) showed improvements on the Metacognition Assessment Scale (MAS-A) scales Self Reflectivity and metacognitive Mastery at follow-up. No effects were found on secondary outcomes. Conclusions: On average, participants in the MERIT group were, based on MAS-A scores, at follow-up more likely to recognize their thoughts as changeable rather than as facts. MERIT might be useful for patients whose self-reflection is too limited to benefit from other therapies. Given how no changes were found in secondary measures, further research is needed. Limitations and suggestions for future research are discussed.